Rancang Bangun Sistem Pendukung Keputusan Penentuan Indeks Lingkungan pada Jaringan Sensor Nirkabel - Muhammad Naufal Prasetyo; Oky Dwi Nurhayati; Eko Didik Widianto (Jurnal Teknologi dan Sistem Komputer, 2016)
Nowadays, the major environmental issues that faced by campus stakeholders is climate change mitigation and campus sustainability. Universities of the world, including in Indonesia, efforts to reduce carbon emissions, manage and improve the development of a sustainable campus. The need for the information of environmental data in the form of gas concentration CO, NO2, particulate matter, temperature, humidity and luminous intensity accurately and real-time using a wireless sensor network. This data is processed using a decision support system to determine the environmental index. This research aims to design a decision support system to determine environmental index on wireless sensor networks. This decision support system is developed using PHP programming language, CodeIgniter framework and MySQL database. The method that used is Simple Additive Weighting (SAW) based on the order of several calculation requirements, the calculation of daily values, the daily scores, geomean of daily scores and weight for each parameter, which in finally is used to determine the environmental index. The results of this research is to show the quality of the environmental index, the graph visualization of environmental index, data for each parameter and the solutions based on index so that it can provide environment information for civitas academica and accurate feedback for decision makers or campus policy to formulate and evaluate policies in a sustainable campus development.